2011
DOI: 10.1002/da.20815
|View full text |Cite
|
Sign up to set email alerts
|

Role of COMT, 5-HT1A, and SERT genetic polymorphisms on antidepressant response to transcranial magnetic stimulation

Abstract: According to our data, 5-HT(1A) polymorphism may play a role in influencing TMS response. The effect of COMT and SERTPR did not reach statistical significance. The analysis of these and other candidate genes in larger samples could help explain genetic influence on TMS response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 57 publications
1
30
1
1
Order By: Relevance
“…In humans, PET imaging of 5-HT1A availability in regions such as the prefrontal cortex (PFC) and insula- areas highly involved in pain regulation- has been associated with the capacity of central suppression of pain [72]. Further attesting to the clinical relevance of such supraspinal 5-HT1A variation, G-carriers were recently reported to experience reduced antidepressant effect of transcranial magnetic stimulation (TMS) focused on the prefrontal cortex (PFC) [27]. These results are paralleled by experiments in rats, where activation of 5-HT1A-receptors in the ventrolateral orbital cortex (VLO) was shown to contribute to descending antinociception [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, PET imaging of 5-HT1A availability in regions such as the prefrontal cortex (PFC) and insula- areas highly involved in pain regulation- has been associated with the capacity of central suppression of pain [72]. Further attesting to the clinical relevance of such supraspinal 5-HT1A variation, G-carriers were recently reported to experience reduced antidepressant effect of transcranial magnetic stimulation (TMS) focused on the prefrontal cortex (PFC) [27]. These results are paralleled by experiments in rats, where activation of 5-HT1A-receptors in the ventrolateral orbital cortex (VLO) was shown to contribute to descending antinociception [73].…”
Section: Discussionmentioning
confidence: 99%
“…In congruence with the outlined effects, the G-allele has been suggested to increase the risk of depression [25], possibly impacting the response to antidepressants [26] and related therapies [27]. There is a substantial comorbidity beween affective disorders and chronic pain [28], [29], [30], indicating overlapping neurobiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical domain, one study investigated the influence of this polymorphism on the antidepressant response in a TMS protocol. Although no effect of the COMT polymorphism was found, the 5-HT1A serotonergic receptor promoter region polymorphism predicted the treatment outcome (Malaguti et al, 2011). In the context of another clinical application, Shivakumar et al (2015) reported a better reduction of auditory hallucinations in schizophrenic patients by tDCS treatment in COMT Val allele homozygous individuals compared to Met allele carriers.…”
Section: Tdcs and The Catechol-o-methyltransferase (Comt)mentioning
confidence: 96%
“…They found that improvement following left sided 10 Hz rTMS treatment correlated positively with changes in 5-HT(2A) receptor binding indices in the DLPFC bilaterally and negatively with right hippocampal binding. Several small case series have implicated genetic polymorphisms that affect serotonin transporter expression, the 5-HT(1A) receptor, or BDNF in modulating the likelihood of response to rTMS, but results have been inconsistent (Zanardi et al, 2007; Bocchio-Chiavetto et al, 2008; Malaguti et al, 2011). In one study, rapid tryptophan depletion did not lead to reemergence of depressive symptoms in adults who had responded to a course of rTMS (O'Reardon et al, 2007), suggesting that the therapeutic effects of rTMS do not depend critically upon central serotonergic tone.…”
Section: Cellular and Neurochemical Effects Of Rtms In Mddmentioning
confidence: 99%